Membentuk Kemandirian Ekonomi Pesantren: Telaah terhadap Peran Kiai dalam Pesantren Al-Amien Prenduan, Madura - Achmad Safiudin R; Supriyanto Supriyanto (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
The role of the Kiai in the independence of the pesantren is very urgent and central. The Kiai determines the pesantren's journey because he has a significant role as the most responsible person. The Kiai is the highest leader in the boarding school structure and has enormous authority. So, the economic independence factor of the pesantren is an essential factor in the future and the determination of the direction of the pesantren by the Kiai. In this study, two problems become the focus of the study: First, how is the role of the Kiai in the economic independence of pesantren. Second, what factors shape financial freedom in Islamic boarding schools. The Al-Amien Prenduan Islamic Boarding School, Sumenep, East Java, focus on this research. This type of research is qualitative research by describing and collecting phenomena and data. Data collection techniques using observation, interviews and documentation. The data analysis method used descriptive analysis. Based on the research conducted, it is known that: first, the role of the Kiai in the economic independence of the pesantren is as a motivator, giver of ideas, advice, provider of capital, management controller, and decision-maker in various regulations that exist in the pesantren business unit that is managed. Second, internal and external factors are two factors that shape economic independence in Islamic boarding schools. Each component, either directly or indirectly, in the pesantren participates in supporting the economy of the pesantren, such as Kiai, administrators, asatidz, santri, and others are internal factors. Meanwhile, the external factor is that the community around the pesantren provides trust and support, such as employees in business units owned by the pesantren and by becoming consumers and investors.